Yield Analysis and Testing of Secondary Metabolite Content in 96% Ethanol Extract of Mint Leaves (Mentha arvensis) - Surahmaida, Surahmaida; Rahmadhany, Wulan Desy (Jurnal Biologi Tropis, 2024)
Medicinal plants are a rich source of secondary metabolites, which have tremendous potential in the development and discovery of new drugs. Mint leaves are used to treat diarrhea and diarrhoea, hypertension, liver and spleen infections, asthma, rheumatic pain, joint irritation, sensitivity and jaundice. The menthol content in natural mint ointment is used in the medicine, perfumery and food businesses. This research aims to determine the yield and content of active secondary metabolite compounds in mint (Mentha arvensis) leaves with an emphasis on alkaloids, flavonoids, tannins, saponins, terpenoids and steroids. The examination strategy uses maceration (watering) techniques for 3 days. Then phytochemical screening was carried out on mint leaves using standard methods. The results showed that the yield of 96% ethanol concentrate from mint leaves was 5.75% and contained a mixture of secondary metabolites of alkaloids, tannins, saponins and steroids.